Integrating Nosampesuvu Values in History Learning as a Conflict Resolution in Central Sulawesi - Misnah, Misnah; Supriatna, Nana; Malla, Hamlan Andi Baso (Paramita: Historical Studies Journal, 2021)
Abstract: This study aims to describe values of local wisdom Nosampesuvu Ethnic Kaili and integrate these values into history learning at SMAN 2 as a conflict resolution in Sigi, Central Sulawesi. Methodologically, this study is qualitative and uses an ethnographic approach. The results of the ethnographic study of the local wisdom values of Nosampesuvu are integrated into learning history using classroom action research (CAR) through the Kemmis and Taggart models. The results showed the findings of ethnographic data of local wisdom values of the Kailiethnic Nosampesuvu group in the integration of the culture of Tolerance ( Mosipahami Patuju) into religious values and social values / cooperation. The uniqueness of the local wisdom of the Kailiethnic Nosampesuvu group was developed in the process of learning local history manifested in cultural values, harmony, polite, polite, friendly, responsible, honest values, and tolerance. The results of the integration found that first, there was an increase in teacher activity in the implementation of learning. Second, there is an increase in student learning outcomes. Thirdly, studentsÃ¢â‚¬â„¢ attitudes toward values Nosampesuvu after implementing local wisdom learning significantly better than before the learning implementation. Thus the implementation of the local wisdom values of Nosampesuvu in local history subjects was successful.Ã‚Â Abstrak: Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai kearifan lokal Suku Nosampesuvu Suku Kaili dan mengintegrasikan nilai-nilai tersebut ke dalam pembelajaran sejarah di SMAN 2 sebagai penyelesaian konflik di Sigi, Sulawesi Tengah. Secara metodologis, penelitian ini bersifat kualitatif dan menggunakan pendekatan etnografi. Hasil kajian etnografi nilai-nilai kearifan lokal Nosampesuvu diintegrasikan ke dalam pembelajaran sejarah dengan menggunakan penelitian tindakan kelas (PTK) melalui model Kemmis dan Taggart. Hasil penelitian menunjukkan temuan data etnografi nilai-nilai kearifan lokal kelompok Kailiethnic Nosampesuvu dalam integrasi budaya Toleransi (Mosipahami Patuju) ke dalam nilai-nilai agama dan nilai-nilai sosial / kerjasama. Keunikan kearifan lokal kelompok Kailiethnic Nosampesuvu dikembangkan dalam proses pembelajaran sejarah lokal yang diwujudkan dalam nilai-nilai budaya, kerukunan, santun, santun, ramah, bertanggung jawab, nilai-nilai kejujuran, dan toleransi. Hasil integrasi menemukan bahwa pertama, terjadi peningkatan aktivitas guru dalam pelaksanaan pembelajaran. Kedua, ada peningkatan hasil belajar siswa. Ketiga, sikap siswa terhadap nilai-nilai Nosampesuvu setelah melaksanakan pembelajaran kearifan lokal secara signifikan lebih baik dibandingkan sebelum pelaksanaan pembelajaran. Dengan demikian penerapan nilai-nilai kearifan lokal Nosampesuvu dalam mata pelajaran sejarah lokal berhasil dilaksanakan.Ã‚Â